Dike channelization and solidification : time scale controls on the geometry and placement of magma migration pathways - Pansino, Stephen (2020)
We investigate the conditions under which magma prefers to migrate through the crust via a dike or a conduit geometry. We performed a series of analogue experiments, repeatedly injecting warm, liquid gelatin, into a cold, solid gelatin medium and allowing the structure to evolve with time. We varied the liquid flux and the time interval between discrete injections of gelatin. The time interval controls the geometry of the migration, in that long intervals allow the intrusions to solidify, favoring the propagation of new dikes. Short time intervals allow the magma to channelize into a conduit. These times are characterized by the Fourier number (Fo), a ratio of time and thermal diffusion to dike thickness, so that long times scales have Fo > 102 and short time scales have Fo < 100. Between these time scales, a transitional behavior exists, in which new dikes nest inside of previous dikes. The flux controls the distance a dike can propagate before solidifying, in that high fluxes favor continual propagation, whereas low fluxes favor dike arrest due to solidification. For vertically propagating dikes, this indicates whether or not a dike can erupt. A transitional behavior exist, in which dikes may erupt at the surface in an unstable, on-and-off fashion. We supplemented the experimental findings with a 2-D numerical model of thermal conduction to characterize the temperature gradient in the crust as a function of intrusion recurrence frequency. For very infrequent intrusions (Fo > 104 to 105) all thermal energy is lost, while more frequent intrusions allow heat to build up nearby.